1992
DOI: 10.1097/00000658-199205000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Ischemic Spinal Cord During Aortic Clamping

Abstract: Infrarenal circumaortic occlusion devices were operatively placed in 74 New Zealand white rabbits. Two days after operation the animals were randomly assigned to one of seven treatment groups: I, control, n = 23; II, halothane, n = 8; III, thiopental, n = 12; IV, ketamine (30 mg/kg intravenously), n = 6; V, halothane+hypothermia, n = 8; VI, thiopental+hypothermia, n = 12; VII, ketamine+hypothermia, n = 5. In each group, the infrarenal aorta was occluded for 21 minutes. Final neurologic recovery after restituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(34 citation statements)
references
References 31 publications
0
30
0
4
Order By: Relevance
“…This did not happen in the present study because laminectomy, which prevents an increase in cerebrospinal fluid pressure, was performed to fix stimulating and recording electrodes. Studies have been carried out to estimate the effects of medications, such as thiopental, ketamine, lidocaine, naloxone, magnesium, methylprednisolone, and tissue factor pathway inhibitor, on transient spinal cord ischemia [37][38][39][40]. Some of these medications showed beneficial effects on spinal cord exposed to ischemia/ reperfusion in animal experiments, but none is accepted as a clinical treatment for patients with spinal cord ischemia or patients who undergo aortic reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This did not happen in the present study because laminectomy, which prevents an increase in cerebrospinal fluid pressure, was performed to fix stimulating and recording electrodes. Studies have been carried out to estimate the effects of medications, such as thiopental, ketamine, lidocaine, naloxone, magnesium, methylprednisolone, and tissue factor pathway inhibitor, on transient spinal cord ischemia [37][38][39][40]. Some of these medications showed beneficial effects on spinal cord exposed to ischemia/ reperfusion in animal experiments, but none is accepted as a clinical treatment for patients with spinal cord ischemia or patients who undergo aortic reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Robertson et al showed that moderate hypothermia (338C) increased the duration of ischemia required to produce neurological deficits in rabbits (Robertson et al, 1986). Hypothermia has been found to improve outcome in several animal models of ischemic SCI, including pigs (Colon et al, 1987;Strauch et al, 2004), rabbits (Naslund et al, 1992;Wakamatsu et al, 1999;Tetik et al, 2002), and dogs (Berguer et al, 1992;Tabayashi et al, 1993) Various new methodologies producing local cooling including epidural cooling techniques have also provided positive results (Yoshitake et al, 2007). In a study by Malatova et al (1995), an epidural cooling technique provided evidence that deep spinal cord hypothermia provided some degree of protection following a regional ischemic insult.…”
Section: Spinal Cord Ischemiamentioning
confidence: 99%
“…Flow is improved with cerebrospinal fluid drainage, 15 and because hypothermia decreases cerebrospinal fluid pressure, improved residual flow may provide sufficient nutritive flow for a relatively prolonged occlusion period before neuronal energy failure. 8 Second, hypothermia is known to diminish clotting which would retard the development, if any, of the evolution of microemboli. Third, ischemia might evoke the release of active factors, such as thromboxane B 2 , which alter vascular tone.…”
Section: Mechanism Of Hypothermia-mediated Protectionmentioning
confidence: 99%